Poetics of Domestic Relationships and Conflicts in the Folk Ballad: Ukrainian-British Context - Karbashevska, O. (Journal of Vasyl Stefanyk Precarpathian National University, 2016)
The paper discusses poetics of the traditional ballad, reflecting family relations and conflicts in Ukrainian and British folklore. This comparative research has its base on the classification of the Ukrainian ballad developed by O. Dei, with the involvement of the systematization of the English ballad by F. Child, is guided by the postulates of O. Dey and G. Gerould as for the plot direction of Ukrainian and British domestic-household ballads, and is focused upon the analysis of the opposition “husband – wife” on the material of Ukrainian songs from the cycle II – B: “Fidelity testing of the family and the spouse”, namely the plot type II – B-1: “the wife (the sweetheart) pretends to be dead and tests her husband (her sweetheart) and relatives” (6 versions, 117 lines), and the English work Child № 29: “The Boy and the Mantle” (1 version, 190 lines). The comparison and analysis of the named texts reveal their typology and uniqueness